2018
DOI: 10.1186/s40168-017-0386-z
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus infection impacts systemic microbiota dynamics and causes quantitative enteric dysbiosis

Abstract: BackgroundMicrobiota integrity is essential for a growing number of physiological processes. Consequently, disruption of microbiota homeostasis correlates with a variety of pathological states. Importantly, commensal microbiota provide a shield against invading bacterial pathogens, probably by direct competition. The impact of viral infections on host microbiota composition and dynamics is poorly understood. Influenza A viruses (IAV) are common respiratory pathogens causing acute infections. Here, we show dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
234
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(275 citation statements)
references
References 58 publications
26
234
1
1
Order By: Relevance
“…Other studies in mice have observed that respiratory virus infection is associated with a change in the gut microbiota, but none have proposed that infection-induced inappetence is the driver (Wang et al, 2014;Deriu et al, 2016;Bartley et al, 2017;Yildiz et al, 2018). Bartley et al (2017) observed that influenza infection drives the gut microbiota composition towards a profile similar to that of calorie restricted mice.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies in mice have observed that respiratory virus infection is associated with a change in the gut microbiota, but none have proposed that infection-induced inappetence is the driver (Wang et al, 2014;Deriu et al, 2016;Bartley et al, 2017;Yildiz et al, 2018). Bartley et al (2017) observed that influenza infection drives the gut microbiota composition towards a profile similar to that of calorie restricted mice.…”
Section: Discussionmentioning
confidence: 98%
“…However, several studies have demonstrated that respiratory infections are associated with a change in the composition of the gut microbiota (Wang et al, 2014;Deriu et al, 2016;Bartley et al, 2017;Groves et al, 2018;Hanada et al, 2018;Yildiz et al, 2018). We have previously observed that viral lung infections alter the gut microbiota, leading to an increase in the relative abundance of Bacteroidetes and a decrease in the relative abundance of Firmicutes (Groves et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Higher diversity and integrity of gut microbiota is favourable to the intestinal ecosystem 41,42 . According to recent research, viral infection can lower microbial diversity in the gut microbiota according to recent research [43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, IAV and RSV have recently been studied in detail. In a recent report, it has been shown that sublethal infection with a low-pathogenic variant of H5N1 IAV can change microbial composition in the LRT (106). The authors show a Bacillus to Lactobacillus shift in the lung microbiome, and interestingly, gut microbiome depletion and disruption of gut barrier integrity and type-1 interferon (IFN-1) response due to lung IAV infection.…”
Section: Viral Infections Of the Lungmentioning
confidence: 99%